2004
DOI: 10.1111/j.1559-1816.2004.tb02572.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Actor‐Observer Effect in Young Drivers' Attributions for Their Own and Their Friends' Risky Driving

Abstract: The attributions of 70 young drivers for their own and their friends' risky driving were examined using open‐ended questions to determine if there were self‐other differences consistent with the actor‐observer effect. Six response categories were created, 4 of which were rated as more dispositional than situational by a subsample of the participants and 2 of which were rated as more situational than dispositional. While the largely dispositional category “Showing off, acting cool” was used significantly more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…These findings support our hypothesis in which we predicted the presence of an extended overall actor-observer effect (Jones & Nisbett, 1971), as well as being compatible with the results of prior research studies (Abramovitch & Freedman, 1981;Harré et al, 2004;Kemdal & Montgomery, 2001;McKay et al, 1989;West, Gunn, & Chernicky, 1975;Wolfson & Salancik, 1977).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings support our hypothesis in which we predicted the presence of an extended overall actor-observer effect (Jones & Nisbett, 1971), as well as being compatible with the results of prior research studies (Abramovitch & Freedman, 1981;Harré et al, 2004;Kemdal & Montgomery, 2001;McKay et al, 1989;West, Gunn, & Chernicky, 1975;Wolfson & Salancik, 1977).…”
Section: Discussionsupporting
confidence: 91%
“…This tendency can be seen when comparing the explanations an individual provides for the same behavioral outcome for self and another, as well as when comparing the explanations one provides for his or her own behavioral outcome to the explanations provided by another individual. Support for the behaviors observed in the actor-observer effect has been shown in attributional patterns comparing self-other explanations for personal preferences (Abramovitch & Freedman, 1981), risky driving behavior (Harré, Brandt, & Houkamau, 2004), alcoholic relapse of spouse (McKay, O'Farrell, Maistro, Connors, & Funder, 1989), comparative explanations of researchers in, and protesters against, animal research (Kemdal & Montgomery, 2001), model racer performance (Wolfson & Salancik, 1977), and decisions to participate in a hypothetical burglary (West, Gunn, & Chernicky, 1975).…”
mentioning
confidence: 91%
“…In a similar vein, novice motorists are typically overconfident about their driving skills (Mynttinen et al, 2009). Many young drivers believe that they engage in less risky driving than their peers (Harré, Brandt, & Houkamau, 2004) and are less likely than their peers to be involved in a collision (Glendon, Dorn, Davies, Matthews, & Taylor, 1996;Matthews & Moran, 1986).…”
Section: Applying the Model To Drivers In Other Jurisdictions And To mentioning
confidence: 99%
“…Although optimism biases are prevalent among all age groups, some studies have suggested that this bias is particularly pronounced among young people in the driving context (Harré et al, 2004;Matthews & Moran, 1986). Overly positive misperceptions about one's own driving skills and abilities may serve to reduce one's tolerance for the objectionable behavior of other road users (Jiang, Li, & Liu, 2008).…”
Section: Applying the Model To Drivers In Other Jurisdictions And To mentioning
confidence: 99%
“…Finn & Bragg, 1986; Guerin, 1994) and causal attribution in young drivers (e.g. Harré, Brandt, & Houkamau, 2004) suggests that there are a number of processes that may disrupt the identification process.…”
Section: Studymentioning
confidence: 99%